Separator for electrochemical device and electrochemical device including the same

By optimizing the distribution of binder particles in the porous coating layer of the separation membrane, the adhesion with the electrode is maintained, addressing the issue of membrane deterioration in electrochemical devices due to electrolyte impregnation, thereby enhancing device performance and reliability.

JP2025502178AActive Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024541706
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-08-18
Publication Date
2025-01-24
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

The adhesion between the separation membrane and the electrode in electrochemical devices deteriorates when impregnated with an electrolytic solution, leading to potential breakage and poor battery performance due to swelling or dissolution of the polymer components in the organic/inorganic composite porous coating layer.

Method used

A porous polymer base material with an organic/inorganic composite porous coating layer containing particulate binder resin and inorganic particles, where the binder particles are distributed such that the content in the upper part of the coating layer is higher than in the center, maintaining adhesion even after electrolyte impregnation, with specific ratios and particle sizes for acrylic and vinylidene fluoride polymer binder particles.

Benefits of technology

The solution maintains strong adhesion between the separation membrane and the electrode in both dry and wet states, preventing performance deterioration and ensuring the integrity of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502178000001_ABST
    Figure 2025502178000001_ABST
Patent Text Reader

Abstract

The present invention relates to a separator for an electrochemical device, which comprises a porous polymer substrate and an organic / inorganic composite porous coating layer formed on at least one surface of the polymer substrate, the porous coating layer comprising a particulate binder resin and inorganic particles, and wherein a ratio of [binder particle content at an upper part of the porous coating layer before impregnation with an electrolyte solution / binder particle content at a central part of the porous coating layer before impregnation with an electrolyte solution]-[binder particle content at an upper part of the porous coating layer after impregnation with an electrolyte solution / binder particle content at a central part of the porous coating layer after impregnation with an electrolyte solution] is 0.32 or less, and an electrochemical device including the separator.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention claims the benefit of the filing date of Patent Application No. 10-2022-0107939, filed with the Korean Intellectual Property Office on August 26, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a separator for an electrochemical device and an electrochemical device including the same, and more particularly, to a separator for an electrochemical device that maintains adhesion to an electrode even when impregnated with an electrolyte, and an electrochemical device including the same. [Background technology]

[0003] Among the components of an electrochemical device, the separator is a porous polymer substrate located between the positive and negative electrodes, which serves to isolate the positive and negative electrodes, prevent electrical shorts between the two electrodes, and allow electrolytes and ions to pass through. Although the separator does not itself participate in the electrochemical reaction, its physical properties, such as wettability with respect to the electrolyte, degree of porosity, and thermal shrinkage rate, affect the performance and safety of the electrochemical device.

[0004] Accordingly, in order to enhance the physical properties of the separator, a coating layer is added to the porous polymer substrate, and various methods have been attempted to change the physical properties of the coating layer by adding various substances to the coating layer. For example, an inorganic substance may be added to the coating layer to improve the mechanical strength of the separator, or an inorganic substance or a hydrate may be added to the coating layer to improve the flame retardancy and heat resistance of the polymer substrate.

[0005] The separator may be attached to the electrode through a lamination process, and a binder resin may be added to the coating layer composition of the separator to ensure adhesion between the electrode and the separator.

[0006] Meanwhile, when the polymer component contained in the organic / inorganic composite porous coating layer coated on the porous polymer substrate is swollen or dissolved by the impregnated electrolyte, the adhesive strength of the porous coating layer to the polymer substrate may decrease, and the function of suppressing the thermal shrinkage of the separator may be deteriorated. In addition, the adhesive strength of the separator to the electrodes may be weakened, which may cause problems in terms of battery cell quality, such as separator breakage and poor appearance of the battery cell. Summary of the Invention [Problem to be solved by the invention]

[0007] The technical problem to be solved by the present invention is to provide a separator for an electrochemical device, which includes an organic / inorganic composite porous coating layer capable of maintaining adhesion between an electrode and a separator even when an electrolyte is injected.

[0008] Another technical problem to be solved by the present invention is to provide an electrochemical device including the above-mentioned separator.

[0009] However, the problems to be solved by the present invention are not limited to the problems described above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0010] According to an embodiment of the present invention for achieving the above object, there is provided a separator for an electrochemical device, comprising: a porous polymer substrate; and an organic / inorganic composite porous coating layer formed on at least one surface of the polymer substrate, wherein the porous coating layer comprises a particulate binder resin and inorganic particles, and a ratio of [content of binder particles in an upper part of the porous coating layer before impregnation with an electrolyte solution / content of binder particles in a central part of the porous coating layer before impregnation with an electrolyte solution]-[content of binder particles in an upper part of the porous coating layer after impregnation with an electrolyte solution / content of binder particles in a central part of the porous coating layer after impregnation with an electrolyte solution] is 0.32 or less.

[0011] The particulate binder resin may be a mixture of acrylic polymer binder particles and vinylidene fluoride polymer binder particles.

[0012] At this time, the weight ratio of the acrylic polymer binder particles to the vinylidene fluoride polymer binder particles may be 7:3 to 3:7.

[0013] The acrylic polymer binder particles may be first copolymer binder particles containing styrene and acrylate in a weight ratio of 5:5 to 7:3.

[0014] In this case, the first copolymer binder particles may have an average particle size of 350 nm or more and 700 nm or less.

[0015] The vinylidene fluoride-based polymer binder particles may be second copolymer binder particles in which vinylidene fluoride-based polymer particles containing 10% by weight or less of hexafluoropropylene (HFP) and acrylate are crosslinked in a weight ratio of 5:5 to 9:1.

[0016] In this case, the average particle size of the second copolymer binder particles may be 150 nm or more and 250 nm or less.

[0017] Also, the particulate binder resin may further include third copolymer particles containing methyl methacrylate and 2-ethylhexyl methacrylate in a weight ratio of 2:8 to 5:5.

[0018] In this case, based on the total content of the particulate binder resin, the acrylic polymer binder particles may be 4 to 95 wt %, the vinylidene fluoride polymer binder particles may be 4 to 95 wt %, and the third copolymer particles may be 1 wt % or more and 10 wt % or less.

[0019] Meanwhile, according to another embodiment of the present invention, there is provided an electrochemical device comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the separator is the separator for an electrochemical device described above. Effect of the Invention

[0020] According to an embodiment of the present invention, the adhesive strength between the separator and the electrodes may be maintained even during the electrolyte impregnation by adjusting the difference between the binder particle content ratio between the upper and central parts of the porous coating layer before the electrolyte impregnation and the binder particle content ratio between the upper and central parts of the porous coating layer after the electrolyte impregnation to be small.

[0021] In addition, even when the separator is immersed in an electrolyte, the particulate polymer binder, which has less swelling, is maintained in a higher content in the upper part than in the center of the porous coating layer, so that the adhesive strength between the separator and the electrode can be maintained even when the separator is immersed in an electrolyte.

[0022] Therefore, the performance of the electrochemical device can be prevented from being deteriorated. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1(A) is a diagram showing the distribution of a binder before electrolyte impregnation depending on the thickness of a porous coating layer of a separator according to one embodiment of the present invention, and FIG. 1(B) is a diagram showing the distribution of a binder after electrolyte impregnation depending on the thickness of a porous coating layer of a separator according to one embodiment of the present invention. [Diagram 2] FIG. 2(A) is a diagram showing the distribution of the binder before electrolyte impregnation depending on the thickness of the porous coating layer of a separator according to a comparative example of the present invention, and FIG. 2(B) is a diagram showing the distribution of the binder after electrolyte impregnation depending on the thickness of the porous coating layer of a separator according to a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, an embodiment of the present invention will be described in detail.

[0025] The embodiments of the present invention described below are provided to more clearly explain the present invention to those having ordinary skill in the art, and the scope of the present invention is not limited to the following embodiments, which may be modified into various other forms.

[0026] The terms used in this specification are used to describe specific embodiments and are not intended to limit the present invention. The singular terms used in this specification may include the plural forms unless the context clearly indicates otherwise. In addition, the terms "comprise" and / or "comprising" used in this specification specify the presence of a mentioned shape, step, number, operation, member, element, and / or group thereof, and do not exclude the presence or addition of one or more other shapes, steps, numbers, operations, members, elements, and / or groups thereof. In addition, the term "connected" used in this specification not only means that a certain member is directly connected, but also includes a concept that includes an indirect connection with another member being further interposed between the members.

[0027] Furthermore, when a member is described herein as being "on" another member, this includes not only when the member is in contact with the other member, but also when there is another member between the two members. The term "and / or" used herein includes any one and all combinations of one or more of the listed items. In addition, terms of degree such as "approximately," "substantially," and the like used herein are used to mean a range of values ​​or degrees or their approximate meanings in consideration of inherent manufacturing and material tolerances, and are used to prevent infringers from unfairly taking advantage of disclosures in which precise or absolute values ​​are recited to aid in the understanding of the present application.

[0028] According to one aspect of the present invention, there is provided a separator for an electrochemical device, comprising a porous polymer substrate and an organic / inorganic composite porous coating layer formed on at least one surface of the polymer substrate, the porous coating layer comprising a particulate binder resin and inorganic particles, and wherein [content of binder particles at an upper part of the porous coating layer before impregnation with an electrolyte solution / content of binder particles at a central part of the porous coating layer before impregnation with an electrolyte solution]-[content of binder particles at an upper part of the porous coating layer after impregnation with an electrolyte solution / content of binder particles at a central part of the porous coating layer after impregnation with an electrolyte solution] (hereinafter referred to as Equation A) is 0.32 or less.

[0029] Here, the upper part of the porous coating layer means a part corresponding to 1 / 3 of the total thickness of the porous coating layer from the surface of the porous coating layer, the central part of the porous coating layer means a part corresponding to 1 / 3 of the total thickness of the porous coating layer from the underside of the upper part of the porous coating layer, and the lower part of the porous coating layer means a part excluding the upper part and the central part.

[0030] In this specification, the thickness of the polymer substrate and / or the porous coating layer can be measured by applying a contact type thickness gauge, for example, Mitutoyo's VL-50S-B.

[0031] In order to obtain excellent adhesion between the electrode and the porous coating layer, it is advantageous that the content of the binder resin in the upper part of the porous coating layer is relatively higher than that in the center part of the porous coating layer. This condition satisfies the following formula.

[0032] [Content of binder particles in the upper part of the porous coating layer / Content of binder particles in the center part of the porous coating layer] (hereinafter referred to as Equation B)>1.0

[0033] In addition, in order to prevent problems such as a decrease in battery performance, the adhesive strength between the electrode and the porous coating layer must be maintained even when the electrolyte is poured in. That is, even when the electrolyte is poured in, the content of the binder resin present in the upper part of the porous coating layer must be greater than that in the center, and in this case, the formula B must be satisfied.

[0034] Meanwhile, generally, after the electrolyte is injected (i.e., in a wet state), the binder component in the porous coating layer is swollen or dissolved by the injected electrolyte, and the adhesive strength of the porous coating layer to the electrode is reduced compared to before the electrolyte is injected (in a dry state). This is believed to be because the binder resin present in the upper part of the porous coating layer migrates toward the center of the porous coating layer due to the electrolyte impregnation, and the content of the binder resin in the upper part of the porous coating layer is relatively reduced.

[0035] However, in order to minimize the decrease in the adhesive strength of the porous coating layer to the electrode even in a wet state, it is preferable that the ratio of the binder particle content in the upper part of the porous coating layer to the binder particle content in the center part in a dry state is maintained at a similar level, and as described above, it is preferable that the formula A is 0.32 or less. If the formula A exceeds 0.32, the adhesive strength of the porous coating layer to the electrode in a wet state may be completely lost.

[0036] Meanwhile, the polymer substrate according to the present invention contains pores that electrically insulate the negative electrode and the positive electrode to prevent short circuiting while allowing lithium ions to pass through, and a porous membrane having high resistance to an electrolytic solution, which is an organic solvent, and a fine pore diameter can be used. The polymer substrate can be used without any particular restrictions as long as it is usable as a separator material for a secondary battery, and can include, for example, polyolefin resins including polyethylene, polypropylene, and polybutene, polyvinyl chloride, polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, polyaramid, nylon, polytetrafluoroethylene, and mixtures or copolymers thereof. Among these, polyolefin resins have excellent applicability of the coating layer slurry, and can reduce the thickness of the separator for a secondary battery, thereby increasing the proportion of the electrode active material layer in the battery and increasing the capacity per volume.

[0037] The thickness of the polymer-based material may be from 1 μm to 100 μm, specifically from 1 μm to 30 μm, and the pore diameter of the polymer-based material may generally be from 0.01 μm to 10 μm.

[0038] In the present invention, the porosity of the polymer-based material may be 30% by volume or more. Specifically, the porosity of the polymer-based material may be 30% by volume or more and 70% by volume or less, 32% by volume or more and 68% by volume or less, 34% by volume or more and 66% by volume or less, 36% by volume or more and 64% by volume or less, 38% by volume or more and 62% by volume or less, 40% by volume or more and 60% by volume or less, 42% by volume or more and 58% by volume or less, 44% by volume or more and 56% by volume or less, 46% by volume or more and 54% by volume or less, or 48% by volume or more and 52% by volume or less. By adjusting the porosity of the polymer-based material within the above range, the movement of ions in the separation membrane can be maintained and an increase in the resistance of the separation membrane can be prevented. Specifically, if the porosity is 70% by volume or less, mechanical properties that can withstand the pressing process for bonding with an electrode can be secured, and the surface opening ratio is not too high, which is suitable for securing adhesive strength. On the other hand, if the porosity is 30% by volume or more, it is advantageous in terms of ion permeability.

[0039] In the present specification, "porosity" refers to the ratio of the volume occupied by pores to the total volume, and is expressed in units of volume %, and may be used interchangeably with terms such as void ratio and porosity. Porosity and pore size may be measured by a BET 6-point method using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porometer, or a porosimetry analyzer (Belsorp-II mini, Bell Japan Inc.) through a nitrogen gas adsorption flow method. In this case, it may be advantageous to use a capillary flow porosimeter.

[0040] A porous coating layer can be formed on the polymer substrate by applying and drying a slurry for forming an organic / inorganic composite porous coating layer, and a surface treatment such as plasma treatment or corona discharge can be performed before applying the slurry to improve impregnation with an electrolyte.

[0041] The porous coating layer includes inorganic particles for improving mechanical properties and insulating properties of the porous polymer substrate, and a binder resin for improving adhesive strength between the electrode and the polymer substrate. The binder resin provides adhesive strength between the electrode and the polymer substrate, and at the same time, bonds adjacent inorganic particles to maintain the bond. The thickness of the porous coating layer may be 0.1 μm or more and 5 μm or less.

[0042] The binder resin according to the present invention may include a particulate binder resin, and such a particulate binder resin may be a mixture of acrylic polymer binder particles and vinylidene fluoride polymer binder particles.

[0043] In this case, the acrylic polymer binder particles may be a polymer containing a carboxylate ester as a repeating unit, and specifically, may be a methacrylate ester. Specific examples of such methacrylic acid esters include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, n-amyl methacrylate, i-amyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, nonyl methacrylate, decyl methacrylate, hydroxymethyl methacrylate, hydroxyethyl methacrylate, ethylene glycol methacrylate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, dipentaerythritol hexamethacrylate, allyl methacrylate, and ethylene dimethacrylate, and the like. The methacrylic acid ester may be one or more selected from among these. Among these, one or more selected from methyl methacrylate, ethyl methacrylate, and 2-ethylhexyl methacrylate are preferred.

[0044] The acrylic polymer binder particles may have a glass transition temperature (Tg) of 60° C. or less, specifically 50° C. or less, and more specifically 40° C. or less. When the acrylic polymer binder particles have a glass transition temperature (Tg) of 60° C. or less, it can be advantageous in improving the adhesive strength of the porous coating layer.

[0045] The vinylidene fluoride-based polymer binder particles are insoluble in an electrolyte solution and may be a homopolymer of vinylidene fluoride, a copolymer of vinylidene fluoride and a different polymerizable monomer, or a mixture of two or more of them.

[0046] The polymerizable monomer other than vinylidene fluoride may be at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, tritrifluoroethylene, chlorofluoroethylene, 1,2-difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3 dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride, but is not limited thereto. In particular, the vinylidene fluoride-based polymer binder particles may be a copolymer of vinylidene fluoride and hexafluoropropylene. The content of the polymerizable monomer other than vinylidene fluoride may be 1% by weight or more and 20% by weight or less of the copolymer, but is not limited thereto.

[0047] In the present invention, the hollow monomer content of the vinylidene fluoride-based polymer binder particles can be measured by 1H-NMR using Varian 500MHz. For details of the measurement method, refer to Journal of Materials Chemistry, 2012, 22, 341 or AMT-3412-0k. The NMR spectrum can be confirmed using a suitable device such as Bruker Avance III HD 700Mhz NMR or Varian 500MHz NMR.

[0048] Here, the weight ratio of the acrylic polymer binder particles to the vinylidene fluoride polymer binder particles may be 7:3 to 3:7. When the content of the acrylic polymer binder particles is greater than the range or the content of the vinylidene fluoride polymer binder particles is less than the range, wet state adhesive strength is not formed, which is not preferable, and when the content of the acrylic polymer binder particles is less than the range or the content of the vinylidene fluoride polymer binder particles is greater than the range, dry state adhesive strength may be difficult to form, which is not preferable. Specifically, the acrylic polymer binder particles have high solubility in the electrolyte, so they are maintained on the upper part of the porous coating layer before being immersed in the electrolyte. The acrylic polymer binder particles maintained in this way can maintain dry adhesive strength during the lamination process of the electrode and the separator, preventing the separator from breaking. When the separator is immersed in the electrolyte, the acrylic polymer binder particles are dissolved in the electrolyte, and the vinylidene fluoride polymer binder particles, which have low solubility in the electrolyte, are maintained on the upper part of the porous coating layer. The vinylidene fluoride polymer binder particles maintained in this manner maintain wet adhesive strength even when immersed in the electrolyte, thereby preventing electrolyte impregnation of the separator and preventing precipitation of lithium dendrites.

[0049] In addition, the acrylic polymer binder particles may be first copolymer binder particles containing styrene and acrylate in a weight ratio of 5:5 to 7:3. Specifically, the first copolymer binder particles may be containing styrene repeating units and acrylate repeating units in a weight ratio of 5:5 to 7:3. In this case, if the styrene content is greater than the above range or the acrylate content is less than the above range, the glass transition temperature (Tg) becomes high, which is not preferable because it may be difficult to form a dry state adhesive strength under the lamination process (50 to 80°C) conditions, and if the styrene content is less than the above range or the acrylate content is greater than the above range, the glass transition temperature (Tg) becomes low, which may cause the binder layer structure to collapse at room temperature, which is not preferable because it may be difficult to form a dry state adhesive strength.

[0050] In this specification, the glass transition temperature can be measured using a differential scanning calorimetry (DSC). Specifically, the glass transition temperature can be measured at a temperature rise rate of 10°C / min (-50°C to 250°C) using a differential scanning calorimetry. For example, the glass transition temperature can be measured using a DSC250 (TA).

[0051] At this time, the average particle size (D 50 ) may be 350 nm to 700 nm, specifically, 350 nm to 500 nm. In this case, if the average particle size of the first copolymer binder particles is smaller than the above range, it is difficult to form a binder layer structure due to soaking between inorganic particles, which is not preferable, and if it exceeds the above range, it is difficult to form and fix a porous coating layer, which is not preferable, and there is a problem in forming a uniform surface.

[0052] Furthermore, the vinylidene fluoride-based polymer binder particles may be second copolymer binder particles in which vinylidene fluoride-based polymer particles containing 10 wt % or less of hexafluoropropylene (HFP) and acrylate are crosslinked in a weight ratio of 5:5 to 9:1. At this time, if the content of the vinylidene fluoride-based polymer particles is greater than the above range or the content of the acrylate is less than the above range, it is difficult to form a wet state adhesive force, which is not preferable, and if the content of the vinylidene fluoride-based polymer particles is less than the above range or the content of the acrylate is greater than the above range, it is difficult to prepare a slurry for forming a porous coating layer, which is not preferable.

[0053] At this time, the average particle size (D 50 ) may be 150 nm or more and 250 nm or less, specifically, 150 nm or more and 200 nm or less. In this case, if the average particle size of the second copolymer binder particles is smaller than the above range, it is difficult to form a binder layer structure due to soaking between inorganic particles, which is not preferable, and if it exceeds the above range, it is not preferable because the porous coating layer may be formed non-uniformly.

[0054] In particular, when the average particle diameters of the first copolymer binder particles and the second copolymer binder particles are all equal, it is more preferable because the adhesive strength in a dry state and a wet state can be uniformly formed between the positive electrode and the negative electrode.

[0055] In this specification, "D 50"Particle size" refers to the particle size at the 50% point of the cumulative particle number distribution according to particle size. The particle size can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution. The particle diameter at the 50% point of the cumulative particle number distribution according to particle size in the measuring device is calculated, and the D 50 The particle size can be measured.

[0056] Meanwhile, the particulate binder resin contained in the porous coating layer may further include third copolymer polymer particles containing methyl methacrylate and 2-ethylhexyl methacrylate in a weight ratio of 2:8 to 5:5. Specifically, it may further include third copolymer polymer particles in which methyl methacrylate and 2-ethylhexyl methacrylate are crosslinked in a weight ratio of 2:8 to 5:5. That is, it may further include third copolymer polymer particles containing methyl methacrylate repeat units and 2-ethylhexyl methacrylate repeat units in a weight ratio of 2:8 to 5:5. At this time, if the content of the methyl methacrylate is greater than the above range or the content of the 2-ethylhexyl methacrylate is less than the above range, the glass transition temperature (Tg) may increase and the peel strength may decrease, which is not preferable. On the other hand, if the content of the methyl methacrylate is less than the above range or the content of the 2-ethylhexyl methacrylate is greater than the above range, the particle shape of the binder may be distorted, which may cause a risk of soaking of the polymer substrate, i.e., the fabric, which is not preferable.

[0057] Here, based on the total content of the particulate binder resin, the acrylic polymer binder particles may be 4 wt % to 95 wt %, the vinylidene fluoride polymer binder particles may be 4 wt % to 95 wt %, and the third copolymer polymer particles may be 1 wt % to 10 wt %. If the contents are outside these ranges, side effects such as increased resistance of the separator and difficulty in forming adhesive force may occur.

[0058] The inorganic particles contained in the porous coating layer according to the present invention are not particularly limited as long as they form the porous coating layer with a uniform thickness and do not cause oxidation and / or reduction reactions within the operating voltage range of the applied electrochemical device. In one embodiment, the uniformity of the thickness may have a tolerance of + / -2 μm. In particular, when inorganic particles having ion transfer ability are used, the ion conductivity in the electrochemical device can be increased to improve performance. In addition, when inorganic particles having a high dielectric constant are used as the inorganic particles, they can contribute to an increase in the dissociation degree of an electrolyte salt, for example, a lithium salt, in the liquid electrolyte, thereby improving the ion conductivity of the electrolyte solution.

[0059] An example of the inorganic particles is an inorganic particle having at least one of the following properties: lithium ion transfer ability, piezoelectricity, and flame retardancy.

[0060] The inorganic particles having good lithium ion transport ability refer to inorganic particles that contain lithium elements but have the function of transporting lithium ions without storing lithium, and the inorganic particles having lithium ion transport ability can transport and transport lithium ions through a type of defect present in the particle structure, thereby improving the lithium ion conductivity in the battery and thereby improving the battery performance.

[0061] Examples of inorganic particles having lithium ion transfer ability include lithium phosphate, lithium titanium phosphate, lithium aluminum titanium phosphate, (LiAlTiP)x O y It can be one or more selected from the group consisting of glass, lithium lanthanum titanate, lithium germanium thiophosphate, lithium nitride such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glass such as Li3PO4-Li2S-SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-based glass such as LiI-Li2S-P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), LLZO-based, or mixtures thereof, but is not limited thereto.

[0062] The inorganic particles having piezoelectricity are insulators under normal pressure, but when a certain pressure is applied, they refer to substances having the property that electricity can pass through due to internal structure changes. They not only exhibit high dielectric constant characteristics with a dielectric constant of 100 or more, but also when a certain pressure is applied and they are stretched or compressed, charges are generated and one side is positively charged and the other side is negatively charged, so that a potential difference is generated between both side surfaces.

[0063] When using inorganic particles having the above characteristics, when an internal short circuit between the positive electrode and the negative electrode occurs due to local pressing (Local crush), external shocks such as nails, the inorganic particles coated on the separator not only prevent the direct contact between the positive electrode and the negative electrode, but also due to the piezoelectricity of the inorganic particles, a potential difference is generated inside the particles. As a result, electron transfer between the positive electrode and the negative electrode, that is, a flow of fine current, is made, thereby achieving a slow decrease in the battery voltage and improving safety thereby.

[0064] Examples of the inorganic particles having piezoelectricity include BaTiO3, Pb(Zr, Ti)O3 (PZT), Pb 1-x La xZr 1-y Ti y O3(PLZT)(0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT) hafnia (HfO2), or mixtures thereof.

[0065] The flame-retardant inorganic particles can prevent overcharging of the electrochemical device, impart flame-retardant properties to the separator, and prevent a sudden rise in temperature inside the battery. The flame-retardant inorganic particles can be at least one selected from the group consisting of antimony-containing compounds, metal hydroxides or hydrates, guanidine-based compounds, boron-containing compounds, and zinc stannate compounds.

[0066] Specifically, the antimony-containing compound may be selected from antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), and antimony pentoxide (Sb2O5); the metal hydroxide or metal hydrate may be selected from alumina (Al2O3), magnesium hydroxide, aluminum hydroxide (Al(OH)3), aluminum oxyhydroxide (AlO(OH)), and CaOAl2O36H2O; the guanidine-based compound may be selected from the group consisting of guanidine nitrate, guanidine sulfamate, guanidine phosphate, and guanyl phosphate; the boron-containing compound may be H3BO3 or HBO2; and the zinc stannate compound may be selected from Zn2SnO4, ZnSnO3, and ZnSn(OH)6.

[0067] Average particle size of inorganic particles (D 50) may be 50 nm to 5000 nm, preferably 200 nm to 1000 nm, more preferably 300 nm to 700 nm. If the average particle size of the inorganic particles is less than 50 nm, the specific surface area increases and more binder resin is required for bonding between the inorganic particles, which is disadvantageous in terms of electrical resistance. Also, the more binder resin is present, the lower the peel strength and binder peeling may be. If the average particle size of the inorganic particles exceeds 5000 nm, the uniformity of the coating layer surface decreases. Also, if the size of the protruding particles after coating is large, the separator and the electrode may be damaged during lamination, causing a short circuit.

[0068] The aspect ratio of the inorganic particles is 1 to 2, preferably 1.2 to 2, and the BET specific surface area of ​​the inorganic particles is 5 m 2 / g or more 25m 2 / g or less. The binder resin can easily move through the gaps between the inorganic particles formed within the above range, and in particular, the smaller the aspect ratio and the smaller the BET specific surface area in the case of monodispersion, the better the movement of the binder resin in the coating layer.

[0069] In the present specification, the BET may be calculated by using the Brunauer-Ennett-Teller model (BET) from the measured N2 adsorption isotherm when the adsorption isotherm is measured up to 1 bar using a BET-specific surface area analyzer (BEL, Microtrac) at -196°C.

[0070] In addition, the porous coating layer may further include a dispersant to further improve the dispersibility of the inorganic particles. The dispersant functions to maintain the inorganic particles in a uniformly dispersed state in the binder resin when preparing a slurry for forming the porous coating layer. Examples of materials that can be used as the dispersant include at least one selected from oil-soluble polyamines, oil-soluble amine compounds, fatty acids, fatty alcohols, sorbitan fatty acid esters, tannic acid, and pyrogallic acid. When a dispersant is included, the porous coating layer may include the dispersant in an amount of 5 wt % or less.

[0071] Meanwhile, in the separator for electrochemical devices according to the present invention, the adhesive strength of the separator in a state in which it is impregnated with an electrolyte, i.e., in a wet state, may be 1.0 gf / 25 mm or more, specifically, 10 gf / 25 mm or more, and more specifically, 15 gf / 25 mm or more and 20 gf / 25 mm or less. If the adhesive strength in a wet state is less than 1.0 gf / 25 mm, the stiffness of the cell may be low, which may cause assembly problems or separator breakage problems during the manufacture of an electrode assembly, and if it exceeds 20 gf / 25 mm, impregnation of the electrolyte into the separator may be hindered, which may cause lithium dendrites to precipitate.

[0072] In the present specification, the wet adhesion strength may be measured by cutting a positive electrode having an NCM-based positive electrode mixture coated on an aluminum foil and the separator to a width of 25 mm, placing the positive electrode in a pouch, injecting a carbonate-based electrolyte, and pressurizing the pouch under conditions of 5 kgf, 70° C., and 4 minutes to prepare a sample for measuring electrode adhesion strength, and then performing a 90° peel test at 200 mm / min using a UTM device from Instron.

[0073] In addition, the separator for electrochemical devices may have an adhesive strength of 10 gf / 25 mm or more before being immersed in an electrolyte, i.e., in a dry state, and more specifically, may have an adhesive strength of 10 gf / 25 mm or more and less than 100 gf / 25 mm, and more specifically, may have an adhesive strength of 30 gf / 25 mm or more and less than 100 gf / 25 mm. If the adhesive strength in a dry state exceeds 100 gf / 25 mm, impregnation of the separator with an electrolyte is hindered, and lithium dendrites may precipitate.

[0074] In the present specification, the dry adhesion strength may be measured by cutting a negative electrode coated with a carbon-based negative electrode mixture on a copper foil and the separator to a width of 25 mm, overlapping the negative electrode and applying pressure at 60° C., 6.5 MPa, and 1 second using a hot press device to prepare a sample for measuring electrode adhesion strength, and then performing a 180° peel test at 300 mm / min using an Instron UTM device.

[0075] Meanwhile, an electrochemical device according to another aspect of the present invention includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and the separator is the separator for an electrochemical device according to the present invention described above.

[0076] In the present invention, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer on at least one surface of the current collector, the positive electrode active material layer including a positive electrode active material, a conductive material, and a polymer binder. The positive electrode active material is a layered compound such as lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M xNi-site type lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B, or Ga and x = 0.01 to 0.3); chemical formula LiMn 1-x M x Lithium manganese composite oxide represented by O2 (where M = Co, Ni, Fe, Cr, Zn, or Ta and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is substituted by alkaline earth metal ions; disulfide compound; It can contain one or a mixture of two or more of Fe2(MoO4)3.

[0077] In the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductive material, and a polymer binder on at least one surface of the current collector. The negative electrode uses, as the negative electrode active material, carbon such as lithium metal oxide, graphitized carbon, and graphite-based carbon; LixFe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Si, SiO x (0 < x < 2), silicon-based materials such as SiC and Si alloys; Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8), etc. metal composite oxides; lithium metal; lithium alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; It can contain one or a mixture of two or more selected from titanium oxides.

[0078] In the present invention, the current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the electrochemical element. For example, stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like may be used.

[0079] In the present invention, the conductive material may be any one selected from the group consisting of graphite, carbon black, carbon or metal fibers, metal powder, conductive whiskers, conductive metal oxides, carbon nanotubes, activated carbon, and polyphenylene derivatives, or a mixture of two or more of these conductive materials. The carbon nanotubes have a graphite sheet with a nano-sized diameter and a cylindrical shape with an sp2 bond structure, and exhibit conductive or semiconductive properties depending on the angle and structure of the graphite sheet. Carbon nanotubes can be classified into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT) according to the bonds forming the walls, and these carbon nanotubes can be appropriately selected depending on the use of the dispersion. More specifically, it may be one or a mixture of two or more conductive materials selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, fanace black, lamp black, summer black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.

[0080] In the present invention, the polymer binder may be any polymer binder commonly used in electrodes in the art. Non-limiting examples of such polymeric binders include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-cotrichloroethylene, polymethylmethacrylate, polyethylhexyl acrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cellulose acetate tetraacet ... Examples of suitable cellulose acetate copolymers include, but are not limited to, cyanoethyl acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxylmethyl cellulose.

[0081] The electrode assembly according to the present invention includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode. The electrode assembly is placed in a suitable case and an electrolyte is injected into the case to manufacture an electrochemical device.

[0082] In the present invention, the electrolyte is + B - A salt having the structure: + Li + , Na + , K + or a combination thereof, such as B - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - Salts containing anions such as or combinations thereof can be dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethylsulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or mixtures thereof.

[0083] The present invention also provides a battery module including a battery having the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool powered by a battery-type motor, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), and the like, electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters), electric golf carts, and power storage systems.

[0084] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various other forms, and the scope of the present invention should not be construed as being limited to the examples described below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0085] <Example 1>

[0086] 10 parts by weight of acrylic polymer binder particles [LGC, AD-S11, D50: 400 nm, copolymer of styrene and butyl acrylate (Tg40°C)], 10 parts by weight of vinylidene fluoride polymer binder particles [Arkema, LBG4330LX, D 50 10 parts by weight of a copolymer of 200 nm, VDF and HFP polymerized in a weight ratio of 95:5 and a copolymer of ethyl acrylate and methyl methacrylate (Tg 20°C) crosslinked in a weight ratio of 7:3], and inorganic particles (Al2O3, D 50 80 parts by weight of 11-methyl-500 nm, Sumitomo, AES11 was added to water and dispersed to prepare a slurry for forming a porous coating layer.

[0087] Next, a porous polymer substrate made of polyethylene (porosity 40 volume%, thickness 9 μm) was prepared, and the slurry was applied to both sides of the surface of the polymer substrate by a bar coating method using a doctor blade, and then dried with hot air at 50°C using a heat gun to form a porous coating layer having a thickness of 12 μm on one side.

[0088] <Example 2>

[0089] A porous coating layer was formed in the same manner as in Example 1, except that the amount of the acrylic polymer binder particles was changed to 14 parts by weight and the amount of the vinylidene fluoride polymer binder particles was changed to 6 parts by weight to prepare a slurry for forming a porous coating layer.

[0090] <Example 3>

[0091] A porous coating layer was formed in the same manner as in Example 1, except that the slurry for forming the porous coating layer was prepared by changing the amount of the acrylic polymer binder particles to 8 parts by weight, the vinylidene fluoride polymer binder particles to 8 parts by weight, and the amount of the polymer binder particles containing methyl methacrylate and 2-ethylhexyl methacrylate in a weight ratio of 5:5 to 4 parts by weight.

[0092] <Comparative Example 1>

[0093] A porous coating layer was formed in the same manner as in Example 1, except that the amount of the acrylic polymer binder particles was changed to 0 parts by weight and the amount of the vinylidene fluoride polymer binder particles was changed to 20 parts by weight to prepare a slurry for forming a porous coating layer.

[0094] <Comparative Example 2>

[0095] A porous coating layer was formed in the same manner as in Example 1, except that the amount of the acrylic polymer binder particles was changed to 20 parts by weight and the amount of the vinylidene fluoride polymer binder particles was changed to 0 parts by weight to prepare a slurry for forming a porous coating layer.

[0096] <Experimental Example 1> Binder Distribution Analysis

[0097] The cross-sections of the porous coating layers of the separators manufactured in the examples and comparative examples are measured using an SEM, and then mapping is performed using EDX analysis. More specifically, the separators are dyed with RuO4, cross-section samples are prepared using ion milling, and then SEM measurements are performed in BSE mode, followed by mapping analysis using EDX. The cross-sections of the porous coating layers are divided into upper, middle, and lower sections, and the areas are calculated through integration to confirm the binder distribution results according to the position of the cross-section of the porous coating layer. Table 1 below numerically shows the binder distribution results according to the cross-section positions of the porous coating layers of the examples and comparative examples.

[0098] [Table 1]

[0099] 1(A) and 1(B) are diagrams showing the distribution of binder depending on the thickness of the porous coating layer of the separator according to Example 1, and FIGS. 2(A) and 2(B) are diagrams showing the distribution of binder depending on the thickness of the porous coating layer of the separator according to Comparative Example 1.

[0100] As shown in Figures 1 and 2, in the case of Example 1, it can be seen that the binder content is maintained higher in the upper part of the porous coating layer than in the center part when comparing before and after the electrolyte impregnation. In the case of Comparative Example 1, it can be seen that the binder content was higher in the upper part of the porous coating layer than in the center part before the electrolyte impregnation, but the binder content was higher in the center part of the porous coating layer than in the upper part after the electrolyte impregnation. As a result, it is expected that the adhesive strength between the porous coating layer and the electrode will decrease after the electrolyte impregnation in the case of Comparative Example 1, but the adhesive strength between the porous coating layer and the electrode will be sufficiently maintained even after the electrolyte impregnation in the case of Example 1.

[0101] <Experimental Example 2> Dry adhesive force measurement

[0102] The negative electrode in which a carbon-based negative electrode mixture is coated on a copper foil and the separator prepared in the above examples and comparative examples are each cut to a width of 25 mm and arranged to overlap each other.

[0103] This was pressurized at 60° C., 6.5 MPa, and 1 second using a hot press to prepare a sample for measuring electrode adhesive strength.

[0104] To measure the adhesive strength between the negative electrode and the separator, a 180° peel test was performed at 300 mm / min using Instron's UTM equipment.

[0105] The dry adhesion thus measured is shown in Table 2 below.

[0106] <Experimental Example 3> Wet adhesive force measurement

[0107] The positive electrode in which the NCM-based positive electrode mixture was coated on the aluminum foil and the separator prepared in the above Examples and Comparative Examples were each cut to a width of 25 mm and placed in a pouch, and a carbonate-based electrolyte was poured into the pouch.

[0108] The pouch was pressurized at 5 kgf, 70° C., and for 4 minutes to prepare a sample for measuring the electrode adhesive strength.

[0109] To measure the adhesive strength between the positive electrode and the separator, a 90° peel test was performed at 20 mm / min using Instron's UTM equipment.

[0110] The wet adhesion strength thus measured is shown in Table 2 below.

[0111] [Table 2]

[0112] Referring to Table 2, in the examples, the dry adhesive strength was measured to be about 40 gf / 25 mm, and the wet adhesive strength was measured to be about 15 to 17 gf / 25 mm, confirming that appropriate and excellent adhesive strength was formed in both dry and wet states. However, in the comparative examples, it can be confirmed that while the dry adhesive strength was formed to some extent, the wet adhesive strength was completely lost.

[0113] In the present specification, preferred embodiments of the present invention are disclosed, and specific terms, for example, are used, but these are used in a general sense to easily explain the technical contents of the present invention and to facilitate understanding of the invention, and are not intended to limit the scope of the present invention. In addition to the embodiments disclosed herein, it is obvious to a person skilled in the art to which the present invention pertains that other modifications based on the technical idea of ​​the present invention can be implemented. For example, a person skilled in the art would know that the separator for an electrochemical device and the electrochemical device including the same according to the embodiments can be modified in various ways. Therefore, the scope of the invention should be determined not by the described embodiments, but by the technical idea described in the claims.

Claims

1. The present invention comprises a porous polymer substrate and an organic / inorganic composite porous coating layer formed on at least one surface of the polymer substrate, The porous coating layer includes a particulate binder resin and inorganic particles, A separator for an electrochemical device, in which the ratio (amount of binder particles in an upper portion of a porous coating layer before impregnation with an electrolyte solution / amount of binder particles in a central portion of a porous coating layer before impregnation with an electrolyte solution) - (amount of binder particles in an upper portion of a porous coating layer after impregnation with an electrolyte solution / amount of binder particles in a central portion of a porous coating layer after impregnation with an electrolyte solution) is 0.32 or less.

2. 2. The separator for an electrochemical device according to claim 1, wherein the particulate binder resin is a mixture of acrylic polymer binder particles and vinylidene fluoride polymer binder particles.

3. 3. The separator for an electrochemical device according to claim 2, wherein a weight ratio of the acrylic polymer binder particles to the vinylidene fluoride polymer binder particles is from 7:3 to 3:

7.

4. 3. The separator for an electrochemical device according to claim 2, wherein the acrylic polymer binder particles are first copolymer binder particles containing styrene and acrylate in a weight ratio of 5:5 to 7:

3.

5. 5. The separator for an electrochemical device according to claim 4, wherein the first copolymer binder particles have an average particle size of 350 nm to 700 nm.

6. 3. The separator for electrochemical devices according to claim 2, wherein the vinylidene fluoride-based polymer binder particles are second copolymer binder particles in which vinylidene fluoride-based polymer particles containing 10 wt % or less of hexafluoropropylene (HFP) and acrylate are crosslinked in a weight ratio of 5:5 to 9:

1.

7. 7. The separator for an electrochemical device according to claim 6, wherein the second copolymer binder particles have an average particle size of 150 nm to 250 nm.

8. 3. The separator for an electrochemical device according to claim 2, wherein the particulate binder resin further comprises third copolymer particles having a weight ratio of methyl methacrylate and 2-ethylhexyl methacrylate of 2:8 to 5:

5.

9. 9. The separator for electrochemical devices according to claim 8, wherein the acrylic polymer binder particles are present in an amount of 4% by weight to 95% by weight, the vinylidene fluoride polymer binder particles are present in an amount of 4% by weight to 95% by weight, and the third copolymer particles are present in an amount of 1% by weight to 10% by weight, based on the total content of the particulate binder resin.

10. An electrochemical element comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being the separator for electrochemical elements according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Separator with improved binding properties to electrodes and electrochemical element equipped therewith

    JP2011512005A

  • Separator and method of manufacturing the same, and lithium secondary battery including the separator

    JP2013235824A

  • Separator for non-aqueous secondary battery and non-aqueous secondary battery

    JP2020155248A

  • Porous film, separator for secondary battery, and secondary battery

    JP2021184378A

  • Separator with a layer of binder polymers for electrochemical device and Electrochemical device comprising the same

    KR1020160069386A